Between vita activa and vita contemplativa Epistolary Forms of otium in Early Modern Italy - Frömmer, Judith; Guidi, Andrea (Mohr Siebeck, 2024)
Zwischen und . Epistolare Formen der Muße im Italien der Frühen Neuzeit.
PublicationDate: 20240408
Keywords: Letters -- Letter Writing -- Intellectual History -- Ricoeur -- Holdinggesellschaft -- Epistolary Culture -- Italian Literature and Culture -- Traffic Law -- Renaissance/Early Modern Cultures -- Sozialität -- Religionsphilosophie -- Religionswissenschaft -- Ethik -- Anthropologie -- Ästhetik -- Kulturphilosophie -- Frühe Neuzeit -- Säkularität/Säkularismus -- Ethics -- Array